Reliability and Qualification of a Floating Gate Memory Manufactured in a Generic Logic Process for RFID Applications - Paulsen, Ron (2006)
In this paper, we discuss the reliability evaluation and qualification results of a small ( 256b) pFET based floating gate nonvolatile memory for embedded application in a UHF RFID chip that is being volume produced using a foundry logic CMOS process. The memory is based on bi-directional Fowler-Nordheim tunneling using a 65-70 Aring oxide that is available from typical foundry processes with 3.3V I/O transistors. Well over one year of retention bake data are reported to show that the memory is reliable for the required applications